The specificity of religious journalism by Valentine Rasputin: from the earthly disappointments to the highest truth - Nikolsky Evgeny Vladimirovich (Studia Humanitatis, 2015)
The article analyses V.G. Rasputin’s journalism specifically marking that his journalism in 1990-s had an image of some non-personified force that consciously managed the processes (like the world government). Other articles by V.G. Rasputin form the view of literature as a way of national identity. He consistently appears as a righteous man and a preacher depending on the stage of aesthetic activities associated with cognition and production of ethical truth. In conclusion the author notes how the writer’s “pochvennichestvo” grew into the oppositional views of the society.